Hotspot testing of glass/backsheet and glass/glass PV modules pre-stressed in extended thermal cycling. (1st January 2023) - Afridi, Muhammad; Kumar, Akash; ibne Mahmood, Farrukh; Tamizhmani, Govindasamy
Highlights: Hotspot stress endurance of two of the latest designs of monocrystalline modules have been investigated: a half-cell glass/backsheet (G/B) module and a full-cell glass/glass (G/G) module. This study differs from the other conventional studies wherein only the fresh modules are subjected to the hotspot endurance stress, while in this study, the modules were aged using extended thermal cycling of 600 cycles (pre-stressed with TC600) before the hotspot test. Results indicate an 8.3% degradation in maximum power of the G/G module, while the G/B module degraded by 1.3%. This suggests that G/B modules having a half-cell design could potentially minimize hotspot degradation and failures in photovoltaic modules. Abstract: This paper investigates the effect of hotspot (HS) stress endurance of two of the latest designs of monocrystalline modules: a half-cell glass/backsheet (G/B) module and a full-cell glass/glass (G/G) module. These modules have already been pre-stressed in extended thermal cycling with 600 cycles per the IEC 61215 standard to represent field-stressed modules. This study differs from the other conventional studies wherein only fresh modules are subjected to hotspot endurance stress. The G/G module reached a maximum temperature of approximately 200 °C at a cell shading of 25 %, 55 °C higher than the maximum hotspot temperature of 145 °C in the G/B module. A significant burn mark, without glass shattering, was observed in the hotspot-stressed cell of the G/G module due to the current mismatch induced by partial shading. Most of the cells in the G/G module appear to be severely damaged (severe dark areas), as observed in the electroluminescence (EL) image, while the dark regions were rarely present in the G/B module. The EL image also illustrates multiple cell cracks that resist current flow and eventually contribute to the full-cell module degradation. About 8.3 % degradation in maximum power was observed for the G/G module and 1.3 % for the G/B module after the sequential stress tests. The lower degradation in the G/B module can potentially be attributed to its design, which comprises of two parallel strings, each having 72-half-cells and benefits from lower heat dissipation. This indicates that the half-cell design could potentially minimize the hotspot degradation and failures in crystalline-silicon modules.